Jovens e adultos: autores de suas próprias palavras - Souza, Jaqueline Silva de [UNESP] (2014)
This research aims to understand the formation of writer subjects and the authorship formation according to a series of activities conducted during one semester of Portuguese classes in a school of Elementary Education of Youth and Adults (EJA) in Campinas-SP. The group of students that participated in this survey was a 4th term, a group of Second Segment of the EJA, which is equal to 9th Grade of Elementary Education II. The interest in this subject arose first by understanding the need for students to be participants in school activities by establishing links between their knowledge and the topics discussed during the classes. Thus, we started from the idea of composing a newspaper, which gave us possibilities to write several genres (BAKTHIN, 1997) and several reflections. This idea was the basis for initiating the major part of the research, which was inspired by the idea of collaborative action research (ELLIOTT, 1998; STENHOUSE, 2008; FIORENTINI, 2008) in partnership with the Portuguese teacher of that school. The data were also produced from the researcher personal journal and personal diaries written by students who participated in this research. Finally, the data analysis was performed from the evidential paradigm (GINZBURG, 1989)